Role of herpes simplex-1, epstein barr and human cytomegalo viruses in aggressive periodontitis - Dani, Sneha; Dwarakanath, CD; Alampalli, Ramesh; Bhat, kishore; AN, Savitha; Gundannavar, Gayatri (Journal of Oral and Dental Sciences, 2013)
Objectives: Aggressive periodontitis is characterized rapid and severe destruction of the tooth supporting tissues with a complex and unclear etiopathogenesis. The present study was designed to identify the role of herpesviruses in pathogenesis of aggressive periodontitis. Material and methods: Study included 15 subjects diagnosed with aggressive periodontitis (group A) and 15 periodontally healthy subjects (group B). Subgingival plaque was collected from the deepest periodontal pocket and gingival tissue biopsy from the adjacent interdental papilla. Results analyzed by polymerase chain reaction. Results: EBV detected in 67% plaque and 73% tissue samples in group A, 7% plaque and none in the tissue samples in group B. HCMV identified in 53% plaque and 20% of tissue samples in group A, 20% plaque and 7% tissue samples in group B. HSV-1 found in 47% plaque and 13% tissue samples in group A, 13% plaque and 47% tissue samples in group B. Conclusion: An increased prevalence of EBV, HCMV and HSV-1 in group A in comparison to healthy controls was observed. Only EBV showed significant difference between both groups. Despite similarity in pathogenic traits between herpesvirus diseases and Periodontitis, delineating the exact role that viruses play in the etiopathogenesis of aggressive periodontitis is difficult.